Effect of corporate governance factors and MSWG activism on cumulative abnormal returns induced by related party transaction - Koay, Chew Chai (2015)
This is an event study that examines the effects of related party transaction (RPT) and corporate governance factors in a firm's daily cumulative abnormal return of the stock price (CAR), using a sample of 422 RPTs engaged by 286 listed firms in the Main Market of Bursa Malaysia from 2008 to 2013. Univariate analysis (t-test) is used to determine the RPT's announcement effect on CAR in the short horizon window, and ordinary least squares (OLS) and logistic regression are employed to investigate the relationships between the W sCA R and exogenous variables of RPT types and size, Minority Shareholder Watchdog Group (MSWG) activism, and corporate governance factors. The univariate result shows significant negative effects on CAR in the postannouncement of RPT, indicating governance discount of stock prices by the market in realizing the occurrence of expropriation, in particular asset acquisition and cash-payment types of RPT. The regression results show that cash ownership of the dominant owner and the divergence of control to cash right for the dominant owner and the directors have a significant negative relationship with CAR. This contributes to extant researches in emerging markets with findings that the problems of expropriation are mainly attributed to circumstances of high dominant family ownerships, which is further exacerbated by the entrenchment of the controlling shareholders and directors. This study also adds to the literature by showing evidence that MSWG activism, which results in higher fm's disclosure quality, has a significant positive effect on CAR in mitigating the expropriating behaviour of the controlling shareholders. Furthermore, the significant positive relationship between board independence and CAR also reinforces previous research findings that increasing the independence of the board enhances its effectiveness as an advocate for minority shareholders' interest. Finally, clear evidence was found that participation of the state's block holders or public investment fund contributes positively to the deterrence of expropriation by the dominant owner.